Ethical issues related to pharmacogenetics: attitudes of pharmacy students - Šesto, Sofija; Šesto, Sara; Krajnović, Dušanka (Archives of Pharmacy, 2022)
Pharmacogenetics is a study of how people respond differently to drug therapy based upon their genes. Available pharmacogenetics tests performed before starting therapy allow each patient to receive the appropriate drug in an adequate dose, in accordance with their genetic status. The aim of this research was to assess the attitudes of pharmacy students about potential ethical issues that may be related to pharmacogenetics testing. This descriptive study was conducted in the period from November to December 2019. Students from all faculties of pharmacy in Serbia filled out a structured questionnaire of 35 questions. A total of 256 respondents, predominantly female (83.8%), studying at the Faculty of Pharmacy – University of Belgrade, participated in the research (88.7%). Most respondents would consider doing a genetic test (78.5%). Of the ethical issues that may be associated with pharmacogenetics testing, students cited patient privacy (27.0%) and data confidentiality (22.7%), or both issues simultaneously (11.3%). Other reasons were forced testing, stigmatization or racial problems (9.8%, 5.1%, 3.5%, respectively). Students of the Faculty of Pharmacy in Belgrade more often recognized all five ethical problems in relation to other faculties and this difference is high statistically significant (χ2 = 68.68, p